(untitled) (Physical Education, Health and Social Sciences, 2025)
This study set out to assess the effect of dietary habits and supplements on nutritional status in women with PCOs of reproductive age in Lahore district. Data was collected using a cross sectional study method from 115 randomly selected women with PCOs. Structured self-administered questionnaire were used to gather data on anthropometric measurements, clinical symptoms, supplementation and dietary habits. The time frame for the research work was 6 months. The data was analyzed by using SPSS version 29.0. In this study the socio demographic data showed that most of the women participating in study were of age 15 to 30 years that is 59.1% while other women fall in the age group of 30 to 55 are 40.9%. According to marital status 17.4% women were unmarried and 82.6% were married. Nutritional status of these 115 women were measured on the basis of their BMI which showed that either they were under weight, normal in weight, overweight or obese. 4.3% women had BMI less than 18 which showed that they were underweight. 44.3% women had BMI in between range 18 to 24.99 which illustrated that they are in the category of healthy nutritional status. 42.6% women had BMI in range 25 to 29.99 that showed that they were overweight while 8.7% had BMI above 30 which showed that they fall in the category of obesity. The intake of fruits and salads was observed mostly in respondents 3 to 6 times a week, most of them were overweight. 66 respondents responded that they consume saturated fats like mutton and egg yolk etc 3 to 6 times week and another 249 responded that they consume twice or thrice a month. The study showed that the highest number of exercise sessions was attended by normal and overweight respondents 2 to 3 times per month. While other respondents in less amount performing exercise sessions 3 to 6 times a week. Lowest number of respondent exercises in each session was once daily.